2014
DOI: 10.1039/c3cp55162h
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the “chemical” nature of the exotic isotopes of hydrogen by the MC-QTAIM analysis: the positively charged muon and the muonic helium as new members of the periodic table

Abstract: This report is a primarily survey on the chemical nature of some exotic species containing the positively charged muon and the muonic Helium, i.e., the negatively charged muon plus helium nucleus, as exotic isotopes of hydrogen, using the newly developed multicomponent quantum theory of atoms in molecules (MC-QTAIM) analysis, employing ab initio non-Born-Oppenhiemer wavefunctions. Accordingly, the "atoms in molecules" analysis performed on various asymmetric exotic isotopomers of hydrogen molecule, recently de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 25 publications
(74 citation statements)
references
References 47 publications
10
64
0
Order By: Relevance
“…In line with the elongation of the oxygen–oxygen internuclear distance, the distance between the Bq center and the oxygen nuclei in structure 3 is approximately 0.05–0.06 Å longer than the corresponding distance in structure 2 . Interestingly, in the previous studies it was also observed that upon replacing a proton with a μ + , independent from the nature of the heavier atom involved in the bond, the mean internuclear distances generally elongate by approximately 0.05 Å . So, this elongation manifests the nature of the μ + and one may conceive structure 3 emerging from replacing the proton of structure 2 by a μ + and upon this isotopic substitution, the transition state transforms into a stable structure.…”
Section: Resultsmentioning
confidence: 88%
“…In line with the elongation of the oxygen–oxygen internuclear distance, the distance between the Bq center and the oxygen nuclei in structure 3 is approximately 0.05–0.06 Å longer than the corresponding distance in structure 2 . Interestingly, in the previous studies it was also observed that upon replacing a proton with a μ + , independent from the nature of the heavier atom involved in the bond, the mean internuclear distances generally elongate by approximately 0.05 Å . So, this elongation manifests the nature of the μ + and one may conceive structure 3 emerging from replacing the proton of structure 2 by a μ + and upon this isotopic substitution, the transition state transforms into a stable structure.…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, the NEO methodology has been also used to study molecular systems containing exotic particles like positrons [13,15,17,42], or the positively charged muons [23][24][25][26]. In the case of the muonic (and positronic) systems the use of the NEO methodology is inevitable from outset since no "safe" adiabatic background has been justified yet and thus any comprehensive "muon-specific computational chemistry" must be based on the NEO.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…, which has also been used in some previous ab initio NEO-HF calculations [23][24][25][26]36], is employed herein. In this function the two parameters, to be determined for each quantum nucleus, are the exponent, n  , and the center of the location of the function in space, , n c R  .…”
Section: Reformulation Of the Neo Based On Thementioning
confidence: 99%
See 1 more Smart Citation
“…I am personally working on the extension of the QTAIM beyond the Born-Oppenhiemer paradigm as well as for exotic species [83], I must emphasize that concomitant topological analysis is central to decipher "atoms in molecules" (AIM) structure in these domains. Traditionally, these domains were not considered to be amenable to AIM analysis so the topological approach of the extended QTAIM (termed multi-component QTAIM) is a novel application of the topological analysis that unifies the AIM concept of a large (and traditionally irrelevant) classes of systems (for a recent example see: [84]). Time-dependent topological analysis is another area that may have a bright future when considering molecular dynamics and time-dependent Schrödinger equation for chemical reactions, even applications beyond chemistry are foreseeable (for some interesting examples of nonorthodox applications of the ELF analysis see: [85,86]).…”
Section: Paolo Lazzeretti Hopefully Yesmentioning
confidence: 99%